Integer Programming and Combinatorial Optimization 18th International Conference, IPCO 2016, Liège, Belgium, June 1-3, 2016, Proceedings - Louveaux, Quentin; Skutella, Martin (Theoretical Computer Science and General Issues, 2016)
This book constitutes the refereed proceedings of the 18th International Conference on Integer Programming and Combinatorial Optimization, IPCO 2016, held in Liège, Belgium, in June 2016. The 33 full papers presented were carefully reviewed and selected from 125 submissions. The conference is a forum for researchers and practitioners working on various aspects of integer programming and combinatorial optimization. The aim is to present recent developments in theory, computation, and applications in these areas. The scope of IPCO is viewed in a broad sense, to include algorithmic and structural results in integer programming and combinatorial optimization as well as revealing computational studies and novel applications of discrete optimization to practical problems.